Adhesive-preventive composition for unvulcanized rubber, aqueous dispersion of adhesive-preventive composition for unvulcanized rubber, and unvulcanized rubber
Patent Information
- Application Number
- JP2021086192
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-05-22
- Filing Date
- 2021-05-21
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-05-21
AI Technical Summary
【0010】 本発明によれば、優れた防着性と設備付着物除去性との両立が可能である未加硫ゴム用防着剤組成物、未加硫ゴム用防着剤組成物水分散液、および未加硫ゴムを提供することができる。
Smart Images

Figure 0007631094000001 
Figure 0007631094000002 
Figure 0007631094000003
Abstract
Description
[Technical field]
[0001] The present invention relates to an adhesion-preventive composition for unvulcanized rubber, an aqueous dispersion of an adhesion-preventive composition for unvulcanized rubber, and unvulcanized rubber. [Background technology]
[0002] At rubber production and processing sites, an anti-adhesion agent is applied to the surface of rubber (for example, unvulcanized rubber) to prevent the rubber from adhering to other surfaces.
[0003] As anti-adhesive agents for rubber, those mainly composed of inorganic powder are widely used. These can generally be used by forming them into an aqueous dispersion and then attaching them to the rubber surface (Patent Documents 1-2). In addition, various anti-adhesive agents using water-soluble polymers and the like have been proposed to reduce dust derived from inorganic powders. For example, Patent Documents 3 and 4 disclose that water-soluble polymers (sodium alginate, CMC, sodium polyacrylate, PVA, etc.), water-soluble polysaccharides (xanthan gum), etc. are blended to increase the viscosity of the aqueous dispersion of the anti-adhesive agent, thereby improving the adhesion of the anti-adhesive agent to the rubber surface. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 50-149770 [Patent Document 2] JP 2013-001720 A [Patent Document 3] Japanese Patent Application Publication No. 62-032127 [Patent Document 4] JP 2009-161667 A Summary of the Invention [Problem to be solved by the invention]
[0005] After the anti-adhesive agent is applied to unvulcanized rubber, the dried anti-adhesive agent may peel off from the surface of the unvulcanized rubber and adhere to the surface of the equipment (e.g., metal surface, etc.) during the application process. If the anti-adhesive agent attached to the equipment (hereinafter sometimes referred to as "equipment attachment") cannot be removed, the equipment attachment may contaminate the equipment and the surrounding environment. Therefore, an anti-adhesive agent for unvulcanized rubber that has excellent properties for easily removing the equipment attachment by physical force (hereinafter sometimes referred to as "equipment attachment removability") is required.
[0006] Therefore, an object of the present invention is to provide an adhesion-preventive composition for unvulcanized rubber, which is capable of achieving both excellent adhesion prevention properties and the ability to remove deposits on equipment, an aqueous dispersion of an adhesion-preventive composition for unvulcanized rubber, and unvulcanized rubber. [Means for solving the problem]
[0007] In order to achieve the above object, the adhesion inhibitor composition for unvulcanized rubber of the present invention comprises: Contains the following components (A) to (C) and water, The component (A) is characterized in that it contains the following components (A1) and (A2). (A) Water-soluble polymer (B) Metal soap (C) Surfactant (A1) Water-soluble polymer other than the following component (A2) (A2) Nonionic cellulose ether
[0008] The aqueous dispersion of the adhesion-preventive composition for unvulcanized rubber of the present invention is characterized by containing the adhesion-preventive composition for unvulcanized rubber of the present invention and water.
[0009] The unvulcanized rubber of the present invention is characterized in that the components (A) to (C) in the adhesion preventive composition for unvulcanized rubber of the present invention are adhered to the surface. Effect of the Invention
[0010] According to the present invention, it is possible to provide an adhesion-preventive composition for unvulcanized rubber, an aqueous dispersion of an adhesion-preventive composition for unvulcanized rubber, and unvulcanized rubber, which are capable of achieving both excellent adhesion prevention properties and the ability to remove deposits on equipment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0011] The present invention will be described in more detail below with reference to examples, but the present invention is not limited to the following description.
[0012] The adhesion-preventive composition for unvulcanized rubber of the present invention may contain, for example, 25 to 70% by mass of the component (A), 20 to 60% by mass of the component (B), and 10 to 20% by mass of the component (C) relative to 100% by mass of the total mass of the components other than water. This allows, for example, a low-cost adhesion-preventive composition for unvulcanized rubber that is excellent in both adhesion prevention and removal of attachments from equipment, and is also excellent in lubricity and scattering properties. Here, in the present invention, "slipperiness" is defined as a property that reduces the frictional resistance generated on the contact surface when an unvulcanized rubber coated with the adhesion-preventive composition for unvulcanized rubber comes into contact with other rubber, metal, or the like. In addition, "scattering property" is defined as a property that the adhesion-preventive composition for unvulcanized rubber and its dried product scatter. The lower the scattering property (the less likely it is to scatter), the more excellent the scattering property of the adhesion-preventive composition for unvulcanized rubber.
[0013] In the present invention, the methods for measuring the adhesion prevention property, removability of material adhering to equipment, slipperiness and scattering property are not particularly limited, but they can be measured, for example, by the methods described in the examples below.
[0014] In the adhesion-preventive composition for unvulcanized rubber of the present invention, for example, the mass ratio (A1) / (A2) of the component (A1) to the component (A2) may be in the range of 1 to 20. This allows, for example, both excellent adhesion prevention properties and removability of deposits on equipment to be achieved, and makes it possible to provide a low-cost adhesion-preventive composition for unvulcanized rubber.
[0015] In the adhesion-preventive composition for unvulcanized rubber of the present invention, for example, the mass ratio (A) / (B) of the component (A) to the component (B) may be in the range of 0.5 to 3. This makes it possible to obtain an adhesion-preventive composition for unvulcanized rubber that can achieve both excellent lubricity and shattering properties.
[0016] The method for preventing adhesion of unvulcanized rubber of the present invention may be, for example, a method for preventing adhesion of unvulcanized rubber, characterized by including an adhesion prevention treatment step of adhering the components (A) to (C) in the adhesion prevention agent composition for unvulcanized rubber of the present invention to the surface of the unvulcanized rubber for adhesion prevention treatment. The adhesion prevention treatment step may be, for example, a step of adhering the adhesion prevention agent composition for unvulcanized rubber of the present invention or an aqueous dispersion of the adhesion prevention agent composition for unvulcanized rubber of the present invention to the surface of the unvulcanized rubber, and further volatilizing water to adhere the components (A) to (C) in the adhesion prevention agent composition for unvulcanized rubber of the present invention to the surface of the unvulcanized rubber. More specifically, the adhesion prevention treatment step may include, for example, an adhesion prevention agent composition attachment step of adhering the adhesion prevention agent composition for unvulcanized rubber of the present invention to the surface of the unvulcanized rubber, and a drying step of drying the adhesion prevention agent composition for unvulcanized rubber on the surface of the unvulcanized rubber to form a coating on the surface of the unvulcanized rubber.
[0017] Specific examples of the present invention will now be described in more detail.
[0018] [1. Anti-adhesive composition for unvulcanized rubber] As described above, the adhesion inhibitor composition for unvulcanized rubber of the present invention comprises: Contains the following components (A) to (C) and water, The component (A) is characterized in that it contains the following components (A1) and (A2). (A) Water-soluble polymer (B) Metal soap (C) Surfactant (A1) Water-soluble polymer other than the following component (A2) (A2) Nonionic cellulose ether
[0019] The anti-adhesive composition for unvulcanized rubber of the present invention contains the above-mentioned components (A) to (C), and therefore can achieve both excellent anti-adhesive properties and the ability to remove deposits on equipment.
[0020] Each component of the adhesion inhibitor composition for unvulcanized rubber of the present invention will be described below.
[0021] [1-1. Component (A): Water-soluble polymer] The component (A) is a water-soluble polymer as described above. In the adhesion-preventive composition for unvulcanized rubber of the present invention, the component (A), i.e., the water-soluble polymer (hereinafter, sometimes referred to as "water-soluble polymer (A)"), is a polymer compound that can be dispersed or dissolved in the adhesion-preventive composition for unvulcanized rubber of the present invention by putting it in water or by heating it after putting it in water. This, for example, provides a coating effect on the unvulcanized rubber, and provides an adhesion-preventive effect. In the adhesion-preventive composition for unvulcanized rubber of the present invention, the content of the water-soluble polymer (A) is not particularly limited, but for example, the lower limit may be 30 mass% or more, for example, 40 mass% or more or 50 mass% or more, relative to the total mass of the components other than water (solid content), and the upper limit is not particularly limited, and may be, for example, 60 mass% or less, 40 mass% or less, or 35 mass% or less. When the content of the water-soluble polymer (A) is 30 mass% or more, relative to the total mass of the components other than water, for example, a coating effect on the unvulcanized rubber is obtained. In addition, since the content of the water-soluble polymer (A) in the adhesion inhibitor composition for unvulcanized rubber of the present invention is 60 mass% or less based on the total mass of components other than water, the adhesion inhibitor composition for unvulcanized rubber of the present invention has, for example, excellent drying properties and can be dried quickly.
[0022] As described above, the component (A) includes the component (A1) and the component (A2). The component (A1) is a water-soluble polymer other than the component (A2), and the component (A2) is a nonionic cellulose ether.
[0023] [1-1-1. Component (A1): Water-soluble polymer other than component (A2)] The component (A1) functions, for example, as a film-forming agent. In addition, for example, the component (A1) and the component (B) are used in combination to exhibit adhesion prevention properties.
[0024] The component (A1) is not particularly limited, but may be, for example, a polymer having a lower limit of solubility of 1 g or more, 10 g or more, or 50 g or more in 100 g of water at 25° C. Furthermore, in the present invention, the “polymer” is not particularly limited, but may have a lower limit of mass average molecular weight of, for example, 1,000 or more, 5,000 or more, or 10,000 or more, and the upper limit of mass average molecular weight is not particularly limited, but may be, for example, 500,000 or less.
[0025] The type of the component (A1) is not particularly limited, and one type may be used alone or multiple types may be used in combination. The component (A1) may be, for example, a synthetic water-soluble polymer or a natural water-soluble polymer. The "synthetic water-soluble polymer" may be, for example, an artificially synthesized polymer having a chemical structure that does not exist in nature, or an artificially synthesized polymer having a chemical structure that exists in nature. The "natural water-soluble polymer" may be, for example, a polymer having a chemical structure that exists in nature that is extracted or produced from nature. The synthetic water-soluble polymer is not particularly limited, and examples thereof include carboxymethylcellulose (CMC), polyacrylic acid, sodium polyacrylate, polyacrylamide, polyvinyl alcohol (PVA), polyvinylpyrrolidone, polyethylene glycol, polyethylene oxide, water-soluble urethane resin, water-soluble melamine resin, water-soluble epoxy resin, water-soluble butadiene resin, and water-soluble phenol resin. Examples of natural water-soluble polymers include, but are not limited to, proteins, xanthan gum, guar gum, welan gum, locust bean gum, diutan gum, tamarind gum, tamarind seed gum, tragacanth gum, gum arabic, carrageenan, rhamsan gum, succinoglycan, tara gum, gellan gum, karaya gum, pectin, alginic acid derivatives, and cellulose ethers.
[0026] The component (A1) is preferably polyvinyl alcohol, carboxymethyl cellulose (CMC), polyacrylic acid, sodium polyacrylate, starches, mannan, alginic acids, natural gums, proteins, polyvinylpyrrolidone, polyethylene glycol, polyethylene oxide, polyacrylamide resin, water-soluble urethane resin, water-soluble melamine resin, water-soluble epoxy resin, water-soluble butadiene resin, water-soluble phenol resin, etc., more preferably at least one selected from the group consisting of polyvinyl alcohol (PVA), CMC, sodium polyacrylate, and polyacrylamide resin, and even more preferably at least one of polyvinyl alcohol and sodium polyacrylate. The viscosity of CMC is preferably 10 to 100,000 mPa·s, more preferably 100 to 100,000 mPa·s, and even more preferably 200 to 90,000 mPa·s in a 2% by mass aqueous solution. The viscosity of PVA is preferably 2 to 500 mPa·s, more preferably 5 to 400 mPa·s, and even more preferably 10 to 200 mPa·s in terms of the viscosity of a 4% by mass aqueous solution. From the viewpoint of improving the adhesion amount of the adhesion-preventive composition for unvulcanized rubber of the present invention to unvulcanized rubber, it is preferable that the viscosity of the component (A1) is not too low. From the viewpoint of improving the drying property of the adhesion-preventive composition for unvulcanized rubber of the present invention, it is preferable that the viscosity of the component (A1) is not too high. In the present invention, the "adhesion amount" of the adhesion-preventive composition for unvulcanized rubber refers to the adhesion amount of all components other than water in the adhesion-preventive composition for unvulcanized rubber to the surface of the unvulcanized rubber.
[0027] The content (mixture amount) of the component (A1) in the adhesion-preventive composition for unvulcanized rubber of the present invention is not particularly limited, but is, for example, 3 to 20 mass%, 4 to 18 mass%, or 5 to 16 mass% relative to the total mass of the adhesion-preventive composition for unvulcanized rubber of the present invention, and is, for example, 25 mass% or more relative to 100 mass% of the total mass of the components other than water (solid content). From the viewpoint of ease of film formation after application of the adhesion-preventive composition for unvulcanized rubber, the content of the component (A1) is, for example, 25 mass% or more, preferably 25 to 75 mass%, more preferably 28 to 70 mass%, and even more preferably 30 to 65 mass% relative to 100 mass% of the total mass of the components other than water. In order to prevent the viscosity of the adhesion-preventive composition for unvulcanized rubber of the present invention from increasing too much and causing deterioration in handling, it is preferable that the content of the component (A1) does not exceed 20 mass% relative to the total mass of the adhesion-preventive composition for unvulcanized rubber of the present invention.
[0028] [1-1-2. Component (A2): Nonionic cellulose ether] As described above, the component (A2) is a nonionic cellulose ether. The component (A2) functions to improve adhesion prevention and remove adhesion from equipment by, for example, a thermal gel effect or by toughening the film of the adhesion-preventive composition for unvulcanized rubber itself. Specifically, for example, the component (A2) thickens the adhesion-preventive composition for unvulcanized rubber of the present invention on the unvulcanized rubber at high temperature immediately after kneading, and it is considered that the adhesion and adhesion prevention of the adhesion-preventive composition for unvulcanized rubber of the present invention are improved. In addition, for example, the combination of the component (A2) and the component (A1) provides an adhesion-preventive composition for unvulcanized rubber that is inexpensive and exhibits high adhesion prevention.
[0029] The type of the component (A2) is not particularly limited, and one type may be used or multiple types may be used in combination. The component (A2) is preferably at least one type selected from the group consisting of alkyl cellulose, hydroxyalkyl cellulose, or hydroxyalkyl alkyl cellulose. In these, the alkyl group is not particularly limited, but for example, a linear or branched alkyl group having 1 to 3 carbon atoms, and may be one type or multiple types of alkyl groups may be mixed. More preferably, the component (A2) is hydroxyalkyl methyl cellulose such as hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, and hydroxybutyl methyl cellulose, alkyl cellulose such as methyl cellulose, ethyl cellulose, and ethyl methyl cellulose, hydroxyalkyl cellulose, and the like, and more preferably, at least one type selected from the group consisting of hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, ethyl methyl cellulose, and hydroxyethyl methyl cellulose, and particularly preferably, at least one type selected from the group consisting of methyl cellulose, ethyl cellulose, and ethyl methyl cellulose.
[0030] The content (amount) of the component (A2) in the adhesion-preventive composition for unvulcanized rubber of the present invention is not particularly limited, but is, for example, 0.05 to 20 mass%, 0.1 to 15 mass%, 0.5 to 10 mass%, or 0.7 to 6 mass% relative to the total mass of the adhesion-preventive composition for unvulcanized rubber of the present invention, and is, for example, 0.1 to 25 mass% relative to 100 mass% of the total mass of the components other than water (solid content). From the viewpoint of ease of film formation after application of the adhesion-preventive composition for unvulcanized rubber, the content of the component (A2) is preferably 0.5 to 20 mass%, more preferably 1 to 15 mass%, relative to 100 mass% of the total mass of the components other than water. In order to prevent the viscosity of the adhesion-preventive composition for unvulcanized rubber of the present invention from increasing too much and causing deterioration in handling, it is preferable that the content of the component (A2) does not exceed 20 mass% relative to the total mass of the adhesion-preventive composition for unvulcanized rubber of the present invention.
[0031] The molar substitution (MS) of the component (A2) is not particularly limited, but is preferably 0.1 to 0.5, more preferably 0.1 to 0.45, and even more preferably 0.1 to 0.4. The molar substitution (MS) is defined as the average number of moles of hydroxypropoxy groups and hydroxyethoxy groups bonded per glucose ring unit of cellulose in the molecule of the component (A2). For example, in the case of methylcellulose, the number of bonded hydroxypropoxy groups and hydroxyethoxy groups is 0, so the molar substitution (MS) is "0".
[0032] The degree of substitution (DS) per glucose of the component (A2) is not particularly limited, but is preferably 1.0 to 4.0, more preferably 1.0 to 3.5, and even more preferably 1.0 to 3.0. The degree of substitution (DS) is defined as the average number of hydroxyl groups substituted with methoxy groups per glucose ring unit of cellulose in the molecule of the component (A2).
[0033] The viscosity of the component (A2) is not particularly limited, but is preferably 10 to 30,000 mPa·s for a 2 mass% aqueous solution, more preferably 100 to 20,000 mPa·s for a 2 mass% aqueous solution, and even more preferably 200 to 15,000 mPa·s for a 2 mass% aqueous solution.
[0034] The mass ratio (A1) / (A2) of the component (A1) to the component (A2) is not particularly limited, but from the viewpoint of achieving both adhesion prevention and low cost, it is preferably in the range of 1 to 30, and the lower limit is more preferably 2 or more, or 3 or more, and the upper limit is more preferably 25 or less, or 20 or less.
[0035] [1-2. Component (B): Metal soap] In the anti-adhesive composition for unvulcanized rubber of the present invention, the component (B) functions, for example, as a lubricant and also functions to increase the dispersibility of the component (A) and improve the anti-adhesive properties.
[0036] The type of component (B) (metal soap (B)) is not particularly limited, and one type may be used alone or multiple types may be used in combination. The metal soap (B) is, for example, a metal salt of a higher fatty acid or a derivative thereof other than a sodium salt or a potassium salt, and is, for example, a salt of the metal salt other than an alkali metal salt. The higher fatty acid is, for example, a fatty acid having 12 or more carbon atoms, and the upper limit of the carbon number is not particularly limited, but is, for example, 20 or less. The derivative of a higher fatty acid may be, for example, a higher fatty acid substituted with one or more substituents. Specific examples of the metal soap (B) include calcium caprylate, zinc caprylate, magnesium caprylate, calcium caprate, zinc caprate, magnesium caprate, calcium laurate, zinc laurate, magnesium laurate, calcium myristate, zinc myristate, magnesium myristate, calcium palmitate, zinc palmitate, magnesium palmitate, calcium stearate, zinc stearate, magnesium stearate, aluminum stearate, aluminum trioctadecanoate, aluminum dioctadecanoate, aluminum monooctadecanoate, calcium octadecanoate, zinc octadecanoate, magnesium octadecanoate, calcium oleate, zinc oleate, magnesium oleate, calcium behenate, zinc behenate, magnesium behenate, 1 Examples of the fatty acids include calcium 2-hydroxystearate, zinc 12-hydroxystearate, magnesium 12-hydroxystearate, calcium 14-octadecanoate, zinc 14-octadecanoate, magnesium 14-octadecanoate, calcium 8-octadecanoate, zinc 8-octadecanoate, magnesium 8-octadecanoate, calcium 6-octadecanoate, zinc 6-octadecanoate, magnesium 6-octadecanoate, calcium coconut fatty acid, zinc coconut fatty acid, magnesium coconut fatty acid, calcium palm oil fatty acid, zinc palm oil fatty acid, magnesium palm oil fatty acid, calcium palm kernel oil fatty acid, zinc palm kernel oil fatty acid, magnesium palm kernel oil fatty acid, calcium beef tallow fatty acid, zinc beef tallow fatty acid, magnesium beef tallow fatty acid, calcium castor oil fatty acid, zinc castor oil fatty acid, and magnesium castor oil fatty acid.
[0037] The metal soap (B) is preferably a divalent metal salt of a fatty acid having an average carbon chain length of 12 to 20, and more preferably a divalent metal salt of a higher fatty acid having a carbon number of 14 to 20 or 16 to 18. The metal soap (B) is preferably a calcium salt, magnesium salt, or zinc salt. Among these, calcium stearate, zinc stearate, and magnesium stearate are preferred from the viewpoint of being widely distributed and easily available at low cost.
[0038] The content (amount) of the metal soap (B) is not particularly limited, but is, for example, 2 to 20 mass% or 3 to 18 mass% based on the total mass of the anti-adhesive composition for unvulcanized rubber of the present invention, and is, for example, 20 to 60 mass% based on the total mass of all components (solids) other than water. When the mass of the metal soap (B) is 20 mass% or more based on the total mass of all components other than water, it is preferable from the viewpoint of the slipperiness of the anti-adhesive coating, and when it is 60 mass% or less, it is preferable from the viewpoint of suppressing powder scattering of the anti-adhesive composition for unvulcanized rubber and suppressing deterioration of handleability due to high viscosity. The content (amount) of the metal soap (B) may be, for example, 25 mass% or more or 30 mass% or more based on the total mass of all components (solids) other than water, and may be, for example, 50 mass% or less, 45 mass% or less, or 40 mass% or less.
[0039] The mass ratio (A) / (B) of the component (A) to the metal soap (B) is not particularly limited, but is, for example, in the range of 0.5 to 6. If it is 0.5 or more, it is easy to suppress powder scattering of the adhesion preventive composition for unvulcanized rubber, and if it is 6 or less, it is easy to obtain an effect of improving adhesion prevention by mixing and dispersing the component (A) and the metal soap (B). The lower limit of the mass ratio (A) / (B) of the component (A) to the metal soap (B) is more preferably 0.6 or more, or 0.8 or more, and the upper limit is more preferably 5 or less, 4 or less, or 3 or less.
[0040] [1-3. Component (C): Surfactant] In the adhesion-preventive composition for unvulcanized rubber of the present invention, the content of the component (C), i.e., the surfactant (hereinafter sometimes referred to as "surfactant (C)") is not particularly limited, but is, for example, 1 to 10 mass%, 2 to 8 mass%, relative to the total mass of the adhesion-preventive composition for unvulcanized rubber of the present invention, and is, for example, 8 to 20 mass% relative to the total mass of all components (solid content) other than water. When the content of the surfactant (C) is 8 mass% or more relative to the total mass of the components other than water, for example, the dispersing effect of the metal soap (B) is improved and separation becomes difficult, and when it is 20 mass% or less, for example, the dispersibility is appropriately suppressed, and the adhesion and adhesion prevention properties are also good. The content of the surfactant (C) may be, for example, 10 mass% or more or 12 mass% or more, and may be, for example, 18 mass% or less or 16 mass% or less, relative to the total mass of the components other than water. The method for measuring the adhesion to unvulcanized rubber is not particularly limited, but can be measured, for example, by the measurement method described in the Examples described later.
[0041] The surfactant (C) imparts dispersibility in water to the anti-adhesive composition for unvulcanized rubber of the present invention, and improves wettability, thereby improving adhesion to unvulcanized rubber. The surfactant (C) is not particularly limited, and may be used alone or in combination of multiple types, for example, at least one of anionic surfactants and nonionic surfactants. The anionic surfactant is not particularly limited, but examples thereof include the following (i) to (iv). The nonionic surfactant is not particularly limited, but examples thereof include the following (v). (i) Carboxylic acid type anionic surfactants such as higher fatty acid salts, alkyl ether carboxylates, polyoxyalkylene ether carboxylates, alkyl (or alkenyl) amide ether carboxylates, and acylamino carboxylates. (ii) Sulfate type anionic surfactants, such as higher alcohol sulfates, polyoxyalkylene higher alcohol sulfates, alkyl phenyl ether sulfates, polyoxyalkylene alkyl phenyl ether sulfates, and glycerin fatty acid ester monosulfates. (iii) Sulfonic acid type anionic surfactants such as alkanesulfonates, α-olefinsulfonates, linear alkylbenzenesulfonates, α-sulfofatty acid ester salts, and dialkylsulfosuccinates. (iv) Phosphate ester type anionic surfactants, such as alkyl phosphate ester salts, polyoxyalkylene alkyl phosphate ester salts, polyoxyalkylene alkylphenyl phosphate ester salts, and glycerin fatty acid ester monophosphate ester salts. (v) Polyoxyalkylene alkyl ether type nonionic surfactants
[0042] The counter ion of the anionic surfactant is not particularly limited, but is preferably an alkali metal such as sodium or potassium, or an alkanolamine such as monoethanolamine or diethanolamine. These may be used alone or in combination.
[0043] As the anionic surfactant, a dialkyl sulfosuccinate is preferred, and dioctyl sulfosuccinate Na is more preferred, since an anti-adhesive composition having superior wettability with the surface of unvulcanized rubber can be obtained.
[0044] The nonionic surfactant is not particularly limited, but in the present invention, for example, a nonionic surfactant represented by the following formula (1) can be used. It is presumed that the nonionic surfactant of the following formula (1), together with the anionic surfactant, not only reduces the surface tension of the adhesion-preventive composition with respect to the surface of the unvulcanized rubber, but also effectively enhances the adhesion of the adhesion-preventive composition to the surface of the unvulcanized rubber. However, this presumption does not limit the present invention in any way. RO-(AO) n -H (1)
[0045] In the formula (1), R represents an aliphatic hydrocarbon group having 8 to 18 carbon atoms. The aliphatic hydrocarbon group may be linear or branched. It may be either saturated or unsaturated. The number of carbon atoms in R is preferably 12 to 16, and more preferably 12 to 13, from the viewpoint of excellent dispersibility of component (A). AO represents an oxyalkylene group having 2 to 4 carbon atoms, and n represents the average number of moles of AO added. n is, for example, 1 to 30 or 1 to 25. Specifically, from the viewpoint of preventing a decrease in the surface activity and a decrease in the dispersibility of the component (A), n is 1 or more (i.e., not 0). Also, from the viewpoint of preventing a decrease in adhesion caused by excessively high hydrophilicity, n is 30 or less or 25 or less. It is presumed that when n is in the range of 1 to 30 or 1 to 25, the dispersibility of the component (A) is further improved, and even when the hydrophobicity of the unvulcanized rubber surface is high, sufficient viscoelasticity is imparted to the dry coating of the adhesion preventive composition for unvulcanized rubber, thereby improving adhesion. However, this presumption does not limit the present invention in any way.
[0046] An oxyalkylene group having 2 to 4 carbon atoms is, for example, a polymer unit formed by the addition of an alkylene oxide having 2 to 4 carbon atoms (formed by addition polymerization). Specific examples of the oxyalkylene group having 2 to 4 carbon atoms include an oxyethylene group (EO) formed by the addition of ethylene oxide, an oxypropylene group (PO) formed by the addition of propylene oxide, and an oxybutylene group (BO) formed by the addition of butylene oxide. (AO) n contains at least an oxyethylene group in its structure. (AO) n When the olefin copolymer contains a plurality of types of oxyethylene groups (EO), oxypropylene groups (PO), and oxybutylene groups (BO), these groups may be arranged in blocks or randomly. n consists of only oxyethylene groups (EO) because it has an excellent balance of hydrophilicity and hydrophobicity.
[0047] Specific examples of nonionic surfactants include, but are not limited to, lauryl ether EO, cetyl ether EO, stearyl ether EO, oleyl ether EO, decyl ether EO, isodecyl ether EO, tridecyl ether EO, secondary alcohol ether EO, synthetic alcohol ether EOPO, lauryl ether EOPO, decyl ether EOPO, isodecyl ether EOPO, tridecyl ether EOPO, and stearyl ether EOPO.
[0048] [1-4.Wed] In the adhesion-preventive composition for unvulcanized rubber of the present invention, the water content is not particularly limited, and may be, for example, 50 mass% or more, 60 mass% or more, or 70 mass% or more, and may be, for example, 90 mass% or less, 85 mass% or less, or 80 mass% or less, relative to the total mass of the adhesion-preventive composition for unvulcanized rubber.
[0049] Water, for example, serves to impart fluidity to the anti-adhesive composition for unvulcanized rubber of the present invention, making it easy to handle. The water is not particularly limited, and may be, for example, tap water, distilled water, ion-exchanged water, etc.
[0050] [1-5. Optional ingredients, etc.] The adhesion inhibitor composition for unvulcanized rubber of the present invention may or may not contain optional components other than the components (A) to (C) and water. For example, the adhesion inhibitor composition for unvulcanized rubber of the present invention may contain additives such as defoamers, preservatives, wettability aids, viscosity aids, and foreign matter reduction aids as optional components, as necessary.
[0051] The defoaming agent is not particularly limited, but examples thereof include oil-based defoaming agents such as castor oil, sesame oil, linseed oil, and animal and vegetable oils; fatty acid ester-based defoaming agents such as isoamyl stearate, distearyl succinate, ethylene glycol distearate, and butyl stearate; alcohol-based defoaming agents such as polyoxyalkylene monohydric alcohol, di-t-amylphenoxyethanol, 3-heptanol, and 2-ethylhexanol; ether-based defoaming agents such as di-t-aminophenoxyethanol, 3-heptyl cellosolve, nonyl cellosolve, and 3-heptyl carbitol; phosphate ester-based defoaming agents such as tributyl phosphate and tris(butoxyethyl)phosphate; amine-based defoaming agents such as diamylamine; amide-based defoaming agents such as polyalkylene amide and acylate polyamine; mineral oil; silicone oil; and the like. Only one type of defoaming agent may be used, or multiple types may be used in combination.
[0052] The preservative is not particularly limited, but for example, a derivative of isothiazolinone can be mentioned. The derivative of isothiazolinone is not particularly limited, but for example, benzisothiazolinone (BIT), methylisothiazolinone (MIT, MI), chloromethylisothiazolinone (CMIT, CMI), octylisothiazolinone (OIT, OI), dichlorooctylisothiazolinone (DCOIT, DCOI) and their derivatives can be mentioned. The preservative may be used alone or in combination of two or more kinds.
[0053] The wettability aid is not particularly limited, but examples thereof include alcohols, and more specifically, examples thereof include methanol, ethanol, hexanol, glycerin, 1,3-butanediol, propylene glycol, dipropylene glycol, pentylene glycol, hexylene glycol, polyethylene glycol, sorbitol, maltitol, sucrose, erythritol, xylitol, polyethylene glycol, polypropylene glycol, ethylene oxide or propylene oxide adducts of polyhydric alcohols, etc. Only one type of the wettability aid may be used, or multiple types may be used in combination.
[0054] The viscosity of the adhesion-preventive composition for unvulcanized rubber of the present invention is not particularly limited, but for reasons of, for example, resistance to separation and good handleability, the viscosity is preferably 25,000 mPa·s or less, more preferably 1,000 to 25,000 mPa·s, still more preferably 2,000 to 25,000 mPa·s, and particularly preferably 3,000 to 24,000 mPa·s, measured at 25°C, 20 rpm, and 10 revolutions using a BH type viscometer three days after the production of the adhesion-preventive composition.
[0055] [2. Method for producing anti-adhesive composition for unvulcanized rubber] The method for producing the anti-adhesive composition for unvulcanized rubber of the present invention is not particularly limited, but for example, it can be produced by mixing all the components of the anti-adhesive composition for unvulcanized rubber (the components (A) to (C) and water, and any optional components that are mixed as necessary). The mixing order and the devices and equipment used for mixing are not particularly limited. For example, a method in which water, a water-soluble polymer (the component (A)), and a surfactant (the component (C)) are mixed, and then a metal soap (the component (B)) and other optional components are mixed can be mentioned. As described above, the device used for mixing is not particularly limited, but for example, a device having a configuration in which a stirring blade is provided in a container can be used. Specifically, for example, liquid mixers such as a general liquid mixer, a vortex mixer, a static mixer, a homogenizer, and a line homomixer can be mentioned.
[0056] [3. Method of using the anti-adhesive composition for unvulcanized rubber] The method of using the adhesion inhibitor composition for unvulcanized rubber of the present invention is not particularly limited, and may be the same as or similar to the method of using a general adhesion inhibitor composition for unvulcanized rubber. The method of using the adhesion inhibitor composition for unvulcanized rubber of the present invention is specifically, for example, as follows, but is not limited thereto.
[0057] The method for preventing adhesion of unvulcanized rubber using the anti-adhesive composition for unvulcanized rubber of the present invention may have an adhesion prevention treatment step in which the components (A) to (C) in the anti-adhesive composition for unvulcanized rubber of the present invention are attached to the surface of the unvulcanized rubber to perform adhesion prevention treatment, as described above. The adhesion to the surface of the unvulcanized rubber can be performed, for example, by a wet method described later. The unvulcanized rubber thus treated for adhesion prevention does not adhere to each other even if it is stored, for example, stacked or folded. In addition, such an anti-adhesive treatment method for unvulcanized rubber can also be said to be, for example, a method for producing anti-adhesive treated unvulcanized rubber.
[0058] The anti-adhesive composition for unvulcanized rubber of the present invention may be used as it is, or may be further diluted with water and used in the form of a water-diluted solution (aqueous dispersion). In the anti-adhesive composition for unvulcanized rubber of the present invention, the concentration when it is attached to the surface of the unvulcanized rubber is not particularly limited, but the total mass of the components other than water may be, for example, 0.5% by mass or more, 1% by mass or more, or 2% by mass or more, and may be, for example, 15% by mass or less, 10% by mass or less, or 5% by mass or less, relative to the total mass of the anti-adhesive composition for unvulcanized rubber. If the concentration is not too high, for example, effects such as low scattering and fast drying can be obtained. If the concentration is not too low, for example, effects such as high adhesion prevention and high slipperiness can be obtained. The anti-adhesive composition for unvulcanized rubber of the present invention can exhibit high adhesion prevention even when the concentration is low when it is attached to the surface of the unvulcanized rubber, so that it can exhibit high adhesion prevention with a small amount of adhesion. The viscosity when applied to the surface of unvulcanized rubber is not particularly limited, and may be, for example, 1 mPa·s or more, 5 mPa·s or more, or 10 mPa·s or more, and may be, for example, 30 mPa·s or less, 20 mPa·s or less, or 15 mPa·s or less. If the viscosity is not too high, for example, effects such as low scattering and fast drying can be obtained. If the viscosity is not too low, for example, effects such as high adhesion resistance and high slipperiness can be obtained.
[0059] The adhesion prevention treatment step may be, for example, as described above, a step of adhering the adhesion-preventive composition for unvulcanized rubber of the present invention or an aqueous dispersion of the adhesion-preventive composition for unvulcanized rubber of the present invention to the surface of the unvulcanized rubber, and further volatilizing the water, thereby adhering the components (A) to (C) in the adhesion-preventive composition for unvulcanized rubber of the present invention to the surface of the unvulcanized rubber. More specifically, the adhesion prevention treatment step may include, for example, an adhesion-preventive composition attachment step for adhering the adhesion-preventive composition for unvulcanized rubber of the present invention to the surface of the unvulcanized rubber, and a drying step for drying the adhesion-preventive composition for unvulcanized rubber on the surface of the unvulcanized rubber to form a coating on the surface of the unvulcanized rubber. Such an adhesion prevention treatment step is called, for example, a wet method. The wet method is not particularly limited, and for example, it can be performed in the same manner as a general wet method for an adhesion-preventive composition for unvulcanized rubber.
[0060] In the step of applying the adhesion-preventive composition for unvulcanized rubber, it is preferable to apply the adhesion-preventive composition for unvulcanized rubber to unvulcanized rubber that is in a high-temperature state (e.g., about 80 to 150°C) due to the heat generated when the unvulcanized rubber is molded into a sheet or the like.
[0061] Specific examples of the method for the adhesion-preventive composition for unvulcanized rubber application step include a method of spraying the adhesion-preventive composition for unvulcanized rubber onto the unvulcanized rubber using a shower device, a dipping method of immersing the unvulcanized rubber in a tank containing the adhesion-preventive composition for unvulcanized rubber for a short period of time, etc. Also, a method of applying the adhesion-preventive composition for unvulcanized rubber onto the unvulcanized rubber using a coating device may be employed, and these methods may be used in combination as appropriate.
[0062] As described above, the anti-adhesive composition for unvulcanized rubber of the present invention can reduce dust, and can exhibit high anti-adhesive properties even with a small amount of adhesion, and can also provide high lubricity.
[0063] The type of rubber to which the anti-adhesive composition for unvulcanized rubber of the present invention can be applied is not particularly limited, and may be any unvulcanized rubber. Examples of the rubber type include natural rubber (NR), butadiene rubber (BR), styrene butadiene rubber (SBR), IIR (butyl rubber), EPDM (ethylene propylene rubber), and the like, and a mixture of two or more of these rubbers.
[0064] As described above, the anti-adhesive composition for unvulcanized rubber and the aqueous dispersion of the anti-adhesive composition for unvulcanized rubber of the present invention can achieve both excellent adhesion prevention and equipment adhesion removal. In addition, the anti-adhesive composition for unvulcanized rubber and the aqueous dispersion of the anti-adhesive composition for unvulcanized rubber of the present invention can achieve, for example, the following effects. First, for example, by not using organic particles, low cost can be achieved. In addition, for example, by using the component (A1) and the component (A2) in combination, excellent adhesion prevention can be exhibited even for natural rubber (NR). In addition, for example, by using the component (A1) and the component (A2) in combination, excellent adhesion prevention can be exhibited even if the dispersibility of the metal soap (B) is reduced when used with high-temperature rubber. EXAMPLES
[0065] Next, examples of the present invention will be described, but the present invention is not limited to the following examples.
[0066] [Example 1] An anti-adhesive composition for unvulcanized rubber of Example 1 was produced as follows.
[0067] First, 710 g of water was placed in a reaction vessel and heated to 80°C or higher. Then, 150 g of polyvinyl alcohol (trade name "Kuraray Poval 60-98", saponification degree 98.0-99.0%, 4% viscosity 54.0-66.0 mPa s, manufactured by Kuraray Co., Ltd.) as component (A1) and 8 g of hydroxypropyl methylcellulose (trade name "Metolose 60SH-4000", methoxy group substitution degree 1.9, hydroxypropoxy group substitution molar number 0.25, 2% viscosity 4000 mPa s, manufactured by Shin-Etsu Chemical Co., Ltd.) as component (A2) were added and mixed for 2 hours, cooled to 30°C or lower, and then stearyl alcohol (trade name "Stearyl 60SH-4000", methoxy group substitution degree 1.9, hydroxypropoxy group substitution molar number 0.25, 2% viscosity 4000 mPa s, manufactured by Shin-Etsu Chemical Co., Ltd.) as component (B) were added and mixed. 100 g of calcium phosphate (manufactured by Taihei Chemical Industry Co., Ltd.), 15 g of coconut alcohol EO adduct (trade name "Leox (registered trademark) CC-150", manufactured by Lion Specialty Chemicals Co., Ltd.) as component (C), 15 g of sodium alpha olefin sulfonate (trade name "Liporan (registered trademark) LB-840", manufactured by Lion Specialty Chemicals Co., Ltd.), and 2 g of preservative (trade name "Topside 609", manufactured by PermaChem Asia Co., Ltd.) were added and stirred to produce the anti-adhesive composition for unvulcanized rubber of Example 1. The obtained anti-adhesive composition for unvulcanized rubber was in a liquid state.
[0068] [Examples 2 to 24, Comparative Examples 1 to 3] Except for changing the types and compositions of the raw materials as shown in Tables 2 to 4 below, the adhesion-preventive compositions for unvulcanized rubber of Examples 2 to 24 and Comparative Examples 1 to 3 were produced in the same manner as in Example 1. The product name (product name), manufacturer, and characteristics (composition) of each raw material used in the production of the adhesion-preventive compositions for unvulcanized rubber of Examples 1 to 24 and Comparative Examples 1 to 3 are shown in Table 1 below.
[0069] [Table 1]
[0070] [Production and performance evaluation of aqueous dispersion of anti-adhesive composition for unvulcanized rubber] The anti-adhesive composition for unvulcanized rubber of each of the Examples and Comparative Examples was diluted 20 times with water to produce an aqueous dispersion of the anti-adhesive composition for unvulcanized rubber (anti-adhesive suspension). This aqueous dispersion of the anti-adhesive composition for unvulcanized rubber was used to perform an anti-adhesive treatment on unvulcanized rubber, and the performances of anti-adhesiveness, lubricity, scattering property, and removability of deposits on equipment were evaluated. The anti-adhesive treatment method and the evaluation method for each of the above-mentioned performances are shown below.
[0071] (1) Rubber for evaluation <Evaluation> In the various evaluations, the following unvulcanized SBR rubber and unvulcanized NR rubber were used as evaluation rubbers. (Unvulcanized SBR rubber) The unvulcanized SBR rubber used was 151.5 parts by mass of unvulcanized SBR rubber (100 parts by mass of SBR (manufactured by Asahi Kasei Corporation, trade name "Tufden 4850"), 30 parts by mass of SAF carbon (manufactured by Mitsubishi Chemical Corporation, trade name "Diablack A"), 15 parts by mass of JSRAROMA (process oil) (manufactured by Japan Sun Oil Co., Ltd., trade name "Aroma 790"), 3 parts by mass of zinc oxide (manufactured by Hakusui Tech Co., Ltd., zinc oxide type 2), 1 part by mass of stearic acid (manufactured by NOF Corp., camellia), 1 part by mass of 6PPD (manufactured by Ouchi Shinko Chemical Industry Co., Ltd., trade name "Nocrac 6C"), 1 part by mass of CBS (manufactured by Ouchi Shinko Chemical Industry Co., Ltd., trade name "Noccela CZ-G"), and 1.5 parts by mass of sulfur (manufactured by Tsurumi Chemical Co., Ltd.). (Unvulcanized NR rubber) The unvulcanized NR rubber used was 100 parts by mass of NR (RSS♯3), 10 parts by mass of white carbon (manufactured by Tosoh Silica Corporation, product name "Nipsil VN-3"), 30 parts by mass of ISAF (Intermediate Super Abrasion Furnace) black (manufactured by Tokai Carbon Co., Ltd., product name "Seat 6"), 15 parts by mass of JSRAROMA (process oil) (manufactured by Japan Sun Oil Co., Ltd., product name "Aroma 790"), 3 parts by mass of zinc oxide (manufactured by Hakusui Tech Co., Ltd., zinc oxide type 2), 1 part by mass of stearic acid (manufactured by NOF Corp., Tsubaki), 1 part by mass of 6PPD (manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Nocrac 6C"), 1 part by mass of CBS (manufactured by Ouchi Shinko Chemical Industry Co., Ltd., product name "Noccela CZ-G"), and 1.5 parts by mass of sulfur (manufactured by Tsurumi Chemical Co., Ltd.) (total of 162.5 parts by mass).
[0072] (2) Evaluation of adhesion prevention The unvulcanized rubber was kneaded with an open roll at a temperature of 80 to 120°C to form a rubber sheet (thickness: 5 to 8 mm, 60 cm x 15 cm), and the rubber sheet immediately after being unwound was immersed for about 1 second in 1 L of an aqueous dispersion of an anti-adhesive composition for unvulcanized rubber (anti-adhesive suspension, temperature 40°C) obtained by diluting the anti-adhesive composition for unvulcanized rubber obtained in each of Examples 1 to 24 and Comparative Examples 1 to 3 20 times with water. Thereafter, the rubber sheet was quickly pulled up vertically, left standing in a vertical state at room temperature, and naturally dried. In this way, the anti-adhesive treatment of the rubber sheet (unvulcanized rubber) was performed.
[0073] The rubber sheet after the adhesion prevention treatment was cut into pieces of 6 cm x 15 cm, and two pieces were stacked together to form a laminated test piece. The laminated test piece was subjected to a force of 1 t / m in the vertical direction from one side. 2 A load of 1000 mm was applied and the sample was left at 60°C for 12 hours.
[0074] After that, the test pieces were returned to room temperature and a 180° peel test was performed using a tensile tester [AGS-500D type, SHIMADZU] to measure the peel resistance (N / cm) at a pulling speed of 300 mm / min. The smaller the peel resistance (N / cm), the better the adhesion resistance.
[0075] (3) Evaluation of lubricity The rubber sheet (unvulcanized rubber) was subjected to anti-adhesion treatment in the same manner as in (2) Evaluation of adhesion resistance. Next, the dried unvulcanized rubber sheet after the anti-adhesion treatment was cut into a 5 x 15 cm rectangle. This rubber was placed on a stainless steel plate, and the plate was gradually tilted to measure the tilt angle at which it slid down. The lower the start of sliding angle, the better the slipperiness.
[0076] (4) Evaluation of scattering The rubber sheet (unvulcanized rubber) was subjected to anti-adhesive treatment in the same manner as in (2) Evaluation of anti-adhesive properties. Next, the dried unvulcanized rubber sheet after the anti-adhesive treatment was cut into a 6 x 15 cm rectangle and weighed. The front and back surfaces of the rubber were brushed 10 times, and the weight was measured again to calculate the amount of scattering. The smaller the amount of scattering, the better the scattering properties.
[0077] (5) Evaluation of equipment deposit removability 15 g of the anti-adhesive composition for unvulcanized rubber of Examples 1 to 24 or Comparative Examples 1 to 3 was applied to an area of 6 x 6 cm of a stainless steel metal plate (SUS304), and dried for 3 hours at 120°C in a hot air dryer to obtain a film of the dried anti-adhesive composition for unvulcanized rubber. After peeling off a part of the dried film, the peeled off part was pinched with tweezers and pulled up with the tweezers, so that the remaining part of the dried film was peeled off from the metal plate as much as possible. Thereafter, the remaining amount of the dried material on the metal plate was visually confirmed and judged on a 5-point scale of 1 to 5 as follows. 1: 0-30% of the area of the metal plate where the dried material was attached has been peeled off. 2: 31-50% of the area of the metal plate where the dried material was attached was peeled off. 3: 51-70% of the area of the metal plate where the dried material was attached was peeled off. 4: 71-90% of the area of the metal plate where the dried material was attached was peeled off. 5: 91-100% of the area of the metal plate where the dried material was attached was peeled off.
[0078] The types and compositions of raw materials in the adhesion-preventive composition for unvulcanized rubber of Examples 1 to 24 and Comparative Examples 1 to 3, and the evaluation results of each performance of adhesion prevention, slipperiness, scattering property, and removability of deposits on equipment, which were evaluated as described above, are summarized in Tables 2 to 4 below. In Tables 2 to 4 below, the numerical values indicating the amount of each raw material (including water) used are the content (mass%) relative to the total mass (including water) of the adhesion-preventive composition for unvulcanized rubber. In addition, "A ratio", "A1 ratio", "A2 ratio", "B ratio", and "C ratio" are numerical values indicating the content (mass%) of component (A), component (A1), component (A2), component (B), and component (C), respectively, relative to 100 mass% of all components other than water in the adhesion-preventive composition for unvulcanized rubber. "A / B" is the ratio obtained by dividing the mass of component (A) by the mass of component (B). "A1 / A2" is the ratio obtained by dividing the mass of component (A1) by the mass of component (A2).
[0079] [Table 2]
[0080] [Table 3]
[0081] [Table 4]
[0082] As shown in Tables 2 to 4, the adhesion-preventive compositions for unvulcanized rubber of Examples 1 to 24 were good in terms of adhesion prevention, slippage, scattering, and equipment deposit removability. In contrast, the adhesion-preventive compositions for unvulcanized rubber of Comparative Examples 1 to 3, which did not use component (A1), component (A2), or component (B), all had inferior equipment deposit removability compared to the Examples. Furthermore, the adhesion-preventive compositions for unvulcanized rubber of Comparative Examples 1 to 3 also had inferior adhesion prevention against natural rubber (NR) compared to the Examples. Furthermore, the adhesion-preventive composition for unvulcanized rubber of Comparative Example 2, which did not use component (A1), had significantly inferior scattering compared to the Examples. The adhesion-preventive composition for unvulcanized rubber of Comparative Example 3, which did not use component (B), had significantly inferior slippage compared to the Examples, and the rubber did not fall off the stainless steel plate even when the stainless steel plate was placed vertically.
Claims
1. Contains the following components (A) to (C) and water, The following component (A) contains the following component (A1) and the following component (A2), Based on 100% by weight of the total weight of ingredients other than water, An anti-adhesive composition for unvulcanized rubber, comprising 25 to 70 mass% of the following component (A), 20 to 60 mass% of the following component (B), and 8 to 20 mass% of the following component (C): (A) A water-soluble polymer other than the following component (C) (B) Metal soap (C) A surfactant other than the component (B) (A1) A water-soluble polymer other than the following component (A2) (A2) Nonionic cellulose ether
2. Based on the total mass of the adhesion inhibitor composition for unvulcanized rubber, 2. The adhesion inhibitor composition for unvulcanized rubber according to claim 1, wherein the water content is 50% by mass or more.
3. 3. The adhesion inhibitor composition for unvulcanized rubber according to claim 1, wherein the mass ratio (A1) / (A2) of the component (A1) to the component (A2) is in the range of 1 to 20.
4. The adhesion inhibitor composition for unvulcanized rubber according to claim 1 , wherein a mass ratio (A) / (B) of the component (A) to the component (B) is in the range of 0.5 to 3.
5. 5. A water-diluted anti-adhesive composition for unvulcanized rubber, comprising the anti-adhesive composition for unvulcanized rubber according to claim 1 and water.
6. 5. An unvulcanized rubber having a surface on which the components (A) to (C) in the adhesion preventive composition for unvulcanized rubber according to any one of claims 1 to 4 are adhered.
Citation Information
Patent Citations
JP1975149770A
Antitack composition for unvulcanized rubber
JP1987032127A
Adhesion-preventive agent composition for unvulcanized rubber and method of producing adhesion-prevented unvolcanized rubber
JP2009161667A
Adhesion-proof agent pack for unvulcanized rubber
JP2010247864A
Anti-adhesion agent for unvulcanized rubber
JP2013001720A